Ekologi Sastra dalam Mitos Panastan di Desa Adat Penestanan Ubud - Dian Saputra, I Made; Indrawan Jendra, Made Iwan; Putu Intan Adelia Ananda Putri; Kartika Sari, Ni Ketut Tirta (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
Abstract This research, entitled "Literary Ecology in the Panastan Myth of the Penestanan Traditional Village Ubud", describes the elements of environmental wisdom and the value of ecological awareness of the Panastan myth. The theories used are literary ecological theory and function theory. The data were collected through observation and interviews, described qualitatively, and presented informally. The Panastan myth contains a pastoral narrative which consists of elements of arcadia construction and elements of retreat and return. In terms of apocalyptic narratives, it can be seen from the elements of hero characters, elements of apocalyptic environments, and elements of vision or prophecy. Meanwhile, using the ethical study model, it was found that there is an attitude of respect and concern for nature, of moral responsibility, solidarity, and love. The myth has been believed to help the maintenance of harmony between the local people and the natural environment. Keywords: Myth, Panastan, and Literary Ecology.